Homestead Food Production (HFP) Model in Suchana. - Huda, Nazmul. (Tufts University. Tisch Library., 2020)
This presentation described a multi-sectoral livelihoods project that is being implemented in Bangladesh.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy